2015
DOI: 10.1039/c5nr02311d
|View full text |Cite
|
Sign up to set email alerts
|

Triggering nanoparticle surface ligand rearrangement via external stimuli: light-based actuation of biointerfaces

Abstract: Bio-molecular non-covalent interactions provide a powerful platform for material-specific self-organization in aqueous media. Here, we introduce a strategy that integrates a synthetic optically-responsive motif with a materials-binding peptide to enable remote actuation. Specifically, we linked a photoswitchable azobenzene moiety to either terminus of a Au-binding peptide. We employed these hybrid molecules as capping agents for synthesis of Au nanoparticles. Integrated experiments and molecular simulations sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
116
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(129 citation statements)
references
References 31 publications
13
116
0
Order By: Relevance
“…In a very recent study, we demonstrated that covalent attachment of an optically-responsive azobenzene moiety to a specific Au-binding peptide (WAGAKRLVLRRE, denoted AuBP1) preserved the optical switching response of the azobenzene, both in solution and when the hybrid biomolecule was adsorbed onto Au NPs. 26 In the adsorbed state, we found that the ratio of the forward and reverse switching rates of the azobenene unit were inverted compared with the ratio for the hybrid molecule free in solution. This indicated that the interaction between the azobenzene and the Au surface influenced the photoswitching kinetics.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…In a very recent study, we demonstrated that covalent attachment of an optically-responsive azobenzene moiety to a specific Au-binding peptide (WAGAKRLVLRRE, denoted AuBP1) preserved the optical switching response of the azobenzene, both in solution and when the hybrid biomolecule was adsorbed onto Au NPs. 26 In the adsorbed state, we found that the ratio of the forward and reverse switching rates of the azobenene unit were inverted compared with the ratio for the hybrid molecule free in solution. This indicated that the interaction between the azobenzene and the Au surface influenced the photoswitching kinetics.…”
Section: Introductionmentioning
confidence: 85%
“…benzamide) (MAM). The MAM molecule was prepared as described in our previous study 26 and in the Supporting Information. Briefly, azobenzene-4,4'-dicarboxylic acid (2.67 g, 9.9 mmol) and thionyl chloride (60 mL) were refluxed overnight to obtain azobenzene-4,4'-dicarboxylic acid chloride, which was then dissolved in methylene chloride (10 mL) and mixed with a solution of N- (2-aminoethyl)maleimide hydrochloride (620 mg, 3.5 mmol) and triethylamine (TEA, 0.7 mL) in methylene chloride (10 mL).…”
Section: Synthesis Of (E)-44'-(diazene-12-diyl)bis(n-(2-(25-dioxo-mentioning
confidence: 99%
“…Incorporation of AB into a larger biomolecular structure offers opportunities to control specific biological targets in vivo, allowing optically-controlled drug release, 7,8 as well as in the field of bionanocombinatorics, where biomolecular non-covalent recognition can be used to assemble ordered nanostructures capable of reconfiguration. [9][10][11][12] Given that many of these applications involve the interface of the photoswitch in contact with a solid surface, elucidation of the structure and properties of AB and its derivatives, adsorbed at material interfaces, is much needed.…”
Section: Introductionmentioning
confidence: 99%
“…22 Recent exploitation of non-covalent metalbiomolecule interactions in this area has included the use of peptides as agents to realise the in-situ nucleation, growth, dispersion, and catalytic activation of NMNPs in aqueous solution. [9][10][11][12][13][14][15] Moreover, the direct non-covalent adsorption of nucleic acid aptamers onto unfunctionalised NMNPs is a key component of successful biomolecular sensor design (see Martin et al 5 for a recent example).…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Moreover, the ability to predictably manipulate the growth morphology of noble metal nanoparticles (NMNPs) in aqueous media via additive-based strategies, especially to produce nonspherical Au NP morphologies, is integral to exerting fine control over NP size and shape. [9][10][11][12][13][14][15] Knowing how and where these additives prefer to bind at the NP interface is key to realizing these strategies 16 .…”
Section: Introductionmentioning
confidence: 99%